Design of electrical system for Billet C8, Blatchford Preston Complex Phase III Al Udeid Air Base, Doha, State of Qatar - Morales, Isidro S. (Manila Professional Regulation Commission, 2015)
Al Udeid Air Base has been identified as an enduring location, its current contingency standard billeting and support facilities (originally built as the base in 2003 for expedient operations; now overcrowded and failing) are being replaced to support a more permanent mission. Of Al Udeid's current population of over 6,900 personnel, approximately 5,635 are still billeted in temporary (contingency-standard) structures and 1,265 are billeted in BPC Phase I billets. In addition, the population will increase when personnel move from Camp Al Sayliyah to Al Udeid Air Base. BPC Phase II is on commissioning stage. Billet C8 is one of the buildings included in the construction packages phase III. It is a client requirement to comply with host country (State of Qatar) requirement of Local Power Authority known as KAHRAMAA and design a high performance sustainable building. Project will be powered by Existing Oil Type Transformer rated 1600kVA, llkV-415/240V, 50 Hz. Incoming feeder (transformer secondary cable) will be provided by KAHRAMAA.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-660G donated by Mr. Jaime E. Mendoza.
Keywords: Buildings -- Electric equipment